Local-Regional Recurrence of Pheochromocytoma/Paraganglioma: Characteristics, Risk Factors and Outcomes - Cui, Yunying; Ma, Xiaosen; Gao, Yinjie; Chang, Xiaoyan; Chen, Shi; Lu, Lin; Tong, Anli (Frontiers in Endocrinology, 2021)
Objective: To study the characteristics, risk factors and outcomes of local-regional recurrence of pheochromocytoma and paraganglioma. Methods: Clinical data were retrospectively analyzed in 96 local-regional recurrent patients and 112 patients without recurrence. Results: Recurrent patients had a median recurrence time of 6.0(4.0, 9.0) years after resection of the primary tumor. SDHB mutation [HR 4.1(1.7, 9.5), p=0.001), primary tumor size 5cm [HR 2.3(1.7, 9.5), p=0.028], and Ki-67 index 3% of primary tumor [HR 2.6(1.7, 9.5), p=0.003] were independent predictors for recurrence in pheochromocytoma and paraganglioma patients. Primary tumor size5cm [HR 5.1(1.7,15.3), p=0.003], and Ki-67 index 3% of primary tumor[HR 2.4(1.1, 5.2), p=0.035] were independent predictors for recurrence of pheochromocytoma, and SDHB mutation [HR 4.6(1.5, 13.9), p=0.007] was predictor for paraganglioma. Among recurrent patients, 47% (45/96) had multiple nodules in recurrent sites, and 58% (56/96) had metastases, 20%( 19/96) were implantation metastases. Compared with the treated patients after recurrence, the risk of metastases (42% vs. 25%, p=0.030) and the risk of death (15% vs. 8%, p=0.003) was significantly increased in the untreated patients. Conclusion: Long-term follow-up in all pheochromocytoma and paraganglioma patients is necessary. The risk factors for recurrence of pheochromocytoma and paraganglioma were different. Primary tumor size, and Ki-67 index were independent predictors for pheochromocytoma patients, and SDHB mutation was predictor for paraganglioma patients. Although the treatment of recurrence was difficult, patients should be treated once recurrence was found.